Reduction and adsorption co-processes for selenate removal by zeolite-supported nanoscale zero-valent iron - Phanthasri, Jakkapop; Yan, Dickson Y.S.; Wantala, Kitirote; Khunphonoi, Rattabal; Tanboonchuy, Visanu (Engineering and Applied Science Research, 2021)
The removal of selenate (Se6+) from aqueous solutions by zeolite Na-P1 supported nanoscale zero-valent iron (Z-NZVI) was investigated. Zeolite was synthesized from the fly ash of the byproducts discharged from coal-fired power, and used as supporting material for NZVI. The synthesized Z-NZVI was characterized using various techniques including x-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM), and BET surface area analysis, and. The results revealed that iron nanoparticles were highly dispersed on the zeolite surfaces which apparently lessened the agglomeration of iron nanoparticles resulting in the enhanced reduction process. The adsorption of Se6+ on Z-NZVI related well with Langmuir isotherm model with maximum adsorption capacity of 15.432 mg·g-1. The experimental results showed that the removal of Se6+ by Z-NZVI increased when the temperature increased. The reactions were found to conform to pseudo second order kinetics. The reaction process occurred spontaneously (-ΔG°), in an endothermic process (ΔH°=29.6 J·mol-1), and with increased randomness (ΔS°=97.17 J·mol-1K-1). This study suggested that Z-NZVI is a promising and efficient material for the selenate removal from wastewater.